2009
DOI: 10.2355/isijinternational.49.957
|View full text |Cite
|
Sign up to set email alerts
|

Formation Conditions of Mg2TiO4 and MgAl2O4 in Ti–Mg–Al Complex Deoxidation of Molten Iron

Abstract: It is important to study the complex deoxidation equilibrium of molten iron in Ti-Mg-Al system from the view point of inclusion control. The equilibrium experiments between molten iron and TiO X -MgO-Al 2 O 3 slag and the thermodynamic calculation on the complex deoxidation are conducted at 1 973 K in the present study. The liquid phase region of TiO X -MgO-Al 2 O 3 system in equilibrium with molten iron is clarified at 1 973 K. The equilibrium compounds which are coexisted with the slag on the liquidus curve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 6 publications
0
11
0
2
Order By: Relevance
“…The calculated stability diagram of Al Ti Mg O system at 1873 K (1600°C) for [Mg] = 3 ppm is shown in Figure 10(b). Simultaneously, the experimental data in the current work and from the literature [39,41,42] Figure 10(b) is more accurate than Figure 10(a) due to all solid inclusion in Table V considered. Figure 10(b) is in accordance with experimental data points.…”
Section: B Thermodynamic Calculation Of Mg-al-ti-o Complex Inclusionsmentioning
confidence: 62%
See 2 more Smart Citations
“…The calculated stability diagram of Al Ti Mg O system at 1873 K (1600°C) for [Mg] = 3 ppm is shown in Figure 10(b). Simultaneously, the experimental data in the current work and from the literature [39,41,42] Figure 10(b) is more accurate than Figure 10(a) due to all solid inclusion in Table V considered. Figure 10(b) is in accordance with experimental data points.…”
Section: B Thermodynamic Calculation Of Mg-al-ti-o Complex Inclusionsmentioning
confidence: 62%
“…[39,41,42] The shaded areas show the liquid phase region calculated using FactSage 6.4 in similar way to Figure 10(c). Figure 11(a) indicates that no Al 2 TiO 5 and Al 2 O 3 inclusions are stably formed with several ppm of [Al] in the molten steel, and there is the stability region The solidification was relatively rapid during the process of samples quenched using water.…”
Section: B Thermodynamic Calculation Of Mg-al-ti-o Complex Inclusionsmentioning
confidence: 98%
See 1 more Smart Citation
“…Modifications of spinel inclusions by a Ti addition and calcium treatment in liquid steel during the refining process were studied by several researchers. [19][20][21][22][23][24][25][26] The formation condition of MgTi2O4 instead of MgAl 2 O 4 was studied by Ono et al 25,26) However, the Ti will accelerate the Mg dissolution from the refractory and slag which will lead to an easier formation of spinel inclusions. 20) Yang et al 22) pointed out that spinel inclusions would transform to liquid complex inclusions, if the dissolved Ca content in the liquid steel exceeds 1 ppm.…”
Section: Introductionmentioning
confidence: 99%
“…5) A determination of the equilibrium relationship between the oxide compounds in MgO-Al 2 O 3 -Ti 2 O 3 and molten iron is important to avoid Al 2 O 3 or MgO · Al 2 O 3 formation and for inclusion control. However, our previous work 6) is the only study that has reported on this and the equilibrium relationship between the deoxidation products and the composition of the solute elements in molten iron was investigated at 1 973 K. Therefore, in this study we investigated the equilibrium relationship between the oxide compounds in MgO-Al 2 O 3 -Ti 2 O 3 and molten iron at 1 873 K.…”
Section: Introductionmentioning
confidence: 99%